32. Teaching Writing Skills That Enhance Student Success in Future Employment - James P. Coyle (Collected Essays on Learning and Teaching, 2011)
The ability to write well is often critical for effective work performance. Although basic writing courses provide a foundation for college and university students, discipline-specific writing tasks and methods are frequently learned indirectly. Incorporating occupational writing skills in course curriculum better prepares students for future employment. This paper suggests a three-step process for teaching pertinent writing skills in college and university courses: identify writing skills relevant to post-graduation occupations, include writing in course learning modules, and assess writing skills with assignments that mirror workplace writing tasks. Balancing curricular learning with these workplace needs is an ongoing challenge for instructors.